Access to shade changes behavioral and physiological attributes of dairy cows during the hot season in the subtropics. (21st May 2015) - Vizzotto, E. F; Fischer, V.; Thaler Neto, A.; Abreu, A. S.; Stumpf, M. T; Werncke, D.; Schmidt, F. A; McManus, C. M.
Abstract : The effect of shade on behavior and physiological attributes of grazing cows in a high altitude subtropical zone is not well established. This work aimed to investigate how social and ingestive behaviors, as well as physiological and other attributes of dairy cows such as milk production, change in a subtropical environment during the hot season either with or without free access to shade. Fourteen lactating cows were kept on pasture either with no shade or with free access to shade for 5 days and their behavior was recorded with instantaneous scan sampled every 10 min, from sunrise, 0530 h (Greenwich mean time, GMT−0200 h) to sunset, 2100 h (GMT−0200 h). Behavior traits included (1) time spent in activities such as grazing, ruminating, resting, lying, standing, walking, seeking shade and staying in the proximity to the water trough and (2) number of events such as water ingestion, aggressive interactions, as well as competition for shade and water. Physiological attributes such as heart and respiratory rates, rectal temperature, number of rumen movements, panting score, as well as milk yield, were evaluated. Time spent in behavioral activities, number of behavioral events and physiological attributes varied between groups (with and without access to shade). Cows with no shade showed increased respiratory and heart rates and panting score at 1300 h, higher values for time of permanence near the water trough, number of competition and aggression events for shade. On the other hand, they showed lower values for time spent resting while lying, ruminating while standing, seeking shade. Access to shade did not change time spent lying, standing, walking with the head up, ruminating while lying, resting while standing, as well as milk yield and number of ruminal movements. Significant interactions between access to shade and days of measurements were detected for time spent walking, ruminating, grazing, resting, number of water ingestion events, competition events near the water trough and for shade, as well as for rectal temperature and panting score measured at 1700 h. In the high altitude subtropical region, access to shade minimizes negative heat stress effects on behavior and physiological aspects of dairy cows.